1986
DOI: 10.1159/000242514
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Retinol Concentrations in Late Pregnancy

Abstract: The concentrations of retinol (vitamin A) were measured in 36 samples of human amniotic fluid obtained near term. Mothers with normal pregnancy had higher amniotic fluid retinol levels than patients with diabetes or toxemia. The results indicate that some maternal complications during pregnancy affect the transport of retinol into amniotic fluid, possibly due to reductions in the uteroplacental blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…One study found that amniotic fluid levels of retinol were higher among normal pregnancies than those with complications such as diabetes and pre‐eclampsia. The authors interpreted their results to suggest that complications may affect transport of retinol into the amniotic fluid, possibly through a mechanism involving poor uteroplacental perfusion . This is consistent with studies by Neel et al., which found that cord serum levels of retinol were positively associated with birthweight, and Ortega‐Senovilla et al., which found that plasma retinol at delivery was higher in mothers with intrauterine growth restriction and that the ratio of umbilical vein plasma levels to maternal levels of retinol were lower in intrauterine growth restriction than appropriate‐for‐gestational‐age controls .…”
Section: Discussionsupporting
confidence: 81%
“…One study found that amniotic fluid levels of retinol were higher among normal pregnancies than those with complications such as diabetes and pre‐eclampsia. The authors interpreted their results to suggest that complications may affect transport of retinol into the amniotic fluid, possibly through a mechanism involving poor uteroplacental perfusion . This is consistent with studies by Neel et al., which found that cord serum levels of retinol were positively associated with birthweight, and Ortega‐Senovilla et al., which found that plasma retinol at delivery was higher in mothers with intrauterine growth restriction and that the ratio of umbilical vein plasma levels to maternal levels of retinol were lower in intrauterine growth restriction than appropriate‐for‐gestational‐age controls .…”
Section: Discussionsupporting
confidence: 81%
“…The role of vitamin A and beta‐carotene (provitamin A) in pregnancy‐induced hypertension and PE is also a subject of controversy. Many clinical studies have found significantly lower levels of vitamin A and beta‐carotene in preeclamptic women than in healthy women 181–185 . However, the decreased levels of retinol and beta‐carotene might be secondary to disease as a part of an acute‐phase reaction rather than a causal relationship.…”
Section: Vitamin Amentioning
confidence: 99%
“…Many clinical studies have found significantly lower levels of vitamin A and beta-carotene in preeclamptic women than in healthy women. [181][182][183][184][185] However, the decreased levels of retinol and betacarotene might be secondary to disease as a part of an acute-phase reaction rather than a causal relationship. Further studies are needed to determine the temporal relationship between carotenoids and the risk of adverse pregnancy outcomes.…”
Section: Vitamin Amentioning
confidence: 99%
“…This decrease was found both in serum 37±40 as well as amniotic¯uid 41 . The constant association between decreased retinol and b-carotene levels with pre-eclampsia, however, does not prove a causal relationship.…”
Section: Resultsmentioning
confidence: 76%
“…Many observational studies found a signi®cant decrease in vitamin A and b-carotene in pre-eclamptic women when compared with normal pregnant women. This decrease was found both in serum 37±40 as well as amniotic¯uid 41 . The constant association between decreased retinol and b-carotene levels with pre-eclampsia, however, does not prove a causal relationship.…”
Section: Vitamin a And Hypertensive Disorders Of Pregnancymentioning
confidence: 76%